Experimental investigation of the effect of coating on surface roughness and drill life in drilling of AISI 4140 steel - Sahin, Omer; Kaluc, Erdinc (MALAYSIAN TRIBOLOGY SOC-MYTRIBOS, 2023)
In this study, the effects of the coating on the hole surface roughness and drill life were investigated in the drilling of AISI 4140 steel workpieces with 14 mm diameter internally cooling uncoated, mono-layer TiN, double-layer AlTiN+TiN and three-layer AlTiN+TiAlN+TiN solid carbide drills on a CNC lathe. Experimental study was carried out with 0.10 and 0.20 mm/rev feed rate and 80 and 90 m/min cutting speed parameters. With the three -layer coating applied to the drills, it is aimed to increase the hole surface quality and cutting tool life. In this study, as a new and different method, the contact areas on the flank face of coated carbide drills were determined. When evaluated in terms of hole surface quality and cutting tool life, they can be listed as three-layer AlTiN+TiAlN+TiN coated solid carbide, double-layer AlTiN+TiN coated solid carbide, mono-layer TiN coated solid carbide and uncoated solid carbide drills, from best to worst. As a result, when comparing uncoated and coated solid carbide drills, coated solid carbide drills have higher chip removal performance, 300% better hole surface quality and 34 times higher cutting tool life.
Keywords: Feed rate; Cutting speed; Surface roughness; Coating; Drilling; Tool life; COATED-CARBIDE; HOLE QUALITY; TWIST DRILLS; PERFORMANCE; PARAMETERS; WEAR; Engineering